Huma Betang's philosophical values in the character of Dayak cultural communication - Rico Rico; Muzahid Akbar Hayat; Khuzaini Khuzaini; Sanusi Sanusi; Didi Susanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Huma Betang is a hereditary heritage, containing philosophical values in the form of brotherly ties, kinship ties and an attitude of tolerance, which is still practiced by the Dayak Tribe. The philosophy of huma betang has seven elements of culture, namely: religious system, social system, knowledge system, language, art, livelihood system, and technology system. This study aims to analyze and find out in depth the preservation, character of cultural communication and the application of cultural values of the huma betang philosophy in the midst of globalization in the Dayak tribe in Mandomai. The researcher used a qualitative method with a descriptive phenomenological study approach. Data obtained from the Dayak tribe in Mandomai by interview technique. From the results of the research obtained, the Dayak tribe in Mandomai is very concerned about preserving the character of cultural communication and the application of cultural values . The philosophy of Huma Betang in the midst of globalization is one of them by making Huma Betang as a model in making homes as a form of planting the meaning contained in the philosophy. The conclusion of this research for the Dayak community is the huma betang philosophy means the same as a view of life that contains religious meaning, believing that we are all God's people, tolerant of the lives of others, learning and teaching knowledge. Whatever the situation, whatever the form of the era as long as the Dayak tribe exists, as long as the huma betang and its philosophy must exist in the life of the Dayak tribe.